OPTIMASI ADSORPSI Cr(VI) PADA SILIKA GEL DARI ABU SEKAM PADI TERMODIFIKASI DIFENILKARBAZIDA (Si-DPZida) - Puspa Dewi Giri, Henny; Sudiarta, I Wayan; Raka Astiti Asih, Ida Ayu (Jurnal Kimia (Journal of Chemistry); Vol. 8, No. 2 Juli 2014DO - 10.24843/JCHEM.2014.v08.i02.p09, 2014)
Adsorption of chromium (VI) on silica gel modified by diphenilcarbazide (Si-DPZida) have been studied. Parameters analyzed were surface acidity by acid-base titration method, specific surface area by absorption of methylene blue method, optimum conditions of adsorption (pH, contact time), and isotherm adsorption. The results showed that Si-DPZida adsorbent has surface acidity (K al ) of 1,5996 mmol/g with the number of active sites of 9,6328 x 10 20 atom/g with specific surface area of 4.4538 m 2 /g. The optimum adsorption process of chromium (VI) by both Si-DPZida occurred at pH 5  and 15 minutes of contact time.  The isotherm adsorptions on both adsorbents tend to follow Freundlich adsorption pattern.
Keywords: adsorptions, silica gel, diphenilcarbazide, chromium (VI)